KtrB-mediated alkaline adaptation drives Enterococcus faecalis persistence in the gastrointestinal tract of Helicoverpa zea - Hurd, Patrick J.; Veto, Vivian; Bell, Geneva; Jackson, Jerreme J. (Frontiers in Microbiology, 2025)
Enterococcus faecalis is a commensal enteric bacterium capable of surviving in extreme and diverse environments. Here, we characterized the role of the gene ntpJ, which encodes the KtrB subunit of the KtrAB Na+/K+ symporter, during the adaptation of E. faecalis to alkaline stress and persistence in Helicoverpa zea (corn earworm). We assessed growth kinetics, biofilm formation, surface adhesion, and gastrointestinal persistence in vivo using an E. faecalis OG1RF mariner transposon mutant (ntpJ-Tn). The ntpJ-Tn mutant showed delayed entry into mid-log phase growth and biofilm formation under standard and alkaline-adjusted conditions relative to the wild-type strain, while adherence to a low-density substrate was not affected, indicating KtrB-mediated transport was important for early-stage planktonic growth but unnecessary for surface attachment. Interestingly, elevated K+ and Na+ ions differentially influenced biofilm morphology and the distribution of adherent cells, highlighting an ion-specific response to alkalinity. The ntpJ-Tn mutant was undetectable 48 hours following ingestion in the novel non-destructive H. zea model, suggesting the loss of KtrB resulted in a persistence defect. These findings reinforce the significance of KtrB-mediated transport in sustaining optimal ionic homeostasis during microbial survival of alkaline stress and demonstrate the efficacy of lepidopteran models for interrogating host-microbe interactions.